Relasi Kuasa Aktivis Perempuan Dalam Kasus Pengambilan Keputusan Di Lembaga Kemahasiswaan Di Fakultas Ilmu Sosial Dan Hukum Universitas Negeri Makassar - Aulia Febrianti Aci; Syukur Muhammad; A.Octamaya Tenri Awaru (Universitas Lambung Mangkurat, 2024)
This type of research is qualitative research and descriptive approach. the number of informants in this study were 8 people who were determined through a purposive sampling technique with the criteria namely 1) student board members at the study program level, 2) female gender. Data collection techniques are observation, interviews and documentation. Checking the validity of the data is done by member check. Data analysis namely data condensation, data model, and drawing conclusions. The results showed that: 1) Forms of Power Relations of Women's Activistsin student organizations at the Study Program Level at the Faculty of Social Sciences and Law, Makassar State University, namely a) power relations over the mind, b) power relations over the body, 2) Factors inhibiting Women's Activistsin building power relations in student organizations at the Study Program Level at the Faculty of Social Sciences and Law, Makassar State University, namely a) patriarchal culture, b) science, c) women's empowerment